UNDERSTANDING CONSUMER PRICE INDEX DYNAMICS IN CANADA - NYONI, Thabani (Theoretical and Practical Research in Economic Fields, 2019)
This research uses annual time series data on Consumer Price Index (CPI) in Canada from 1960 to 2017, to model and forecast CPI using the Box – Jenkins ARIMA technique. Diagnostic tests indicate that the C series is I (1). The study presents the ARIMA (1, 1, 1) model for predicting CPI in Canada. The diagnostic tests further show that the presented parsimonious model is stable. The results of the study apparently show that CPI in Canada is likely to continue on a sharp upwards trajectory in the next decade. The study encourages policy makers to make use of tight monetary and fiscal policy measures in order to control inflation in Canada.